1998
DOI: 10.1111/j.1440-1843.1998.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of bronchoalveolar lavage and postbronchoscopic sputum cytology in peripheral lung cancer

Abstract: The objective of this study was to evaluate the value of bronchoalveolar lavage (BAL) and postbronchoscopic sputum cytology in diagnosing peripheral lung cancer. We performed a prospective study in 55 patients with lesions on chest radiographs who were suspected of having lung cancer and had non-endoscopically visible lesions on fiberoptic bronchoscopy. The sequence of procedures in all cases was BAL and transbronchial forceps biopsy. The final diagnosis of these patients were primary lung cancer in 30 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 15 publications
4
27
1
Order By: Relevance
“…Similar results were achieved by Wongsurakiat et al 29 They had a lot of false negatives in their study. They reported that in five patients with metastatic lung cancer BAL gave negative results in all.…”
Section: 22supporting
confidence: 79%
See 2 more Smart Citations
“…Similar results were achieved by Wongsurakiat et al 29 They had a lot of false negatives in their study. They reported that in five patients with metastatic lung cancer BAL gave negative results in all.…”
Section: 22supporting
confidence: 79%
“…In our study tumor categorisation was done by BAL in approximately 25% cases which is comparable to the study done by Gaur et al but at variance to the study done by Pirozynski, Wongsurkiat et al 28,29,30 (Table 5). In the present study, 270 were correctly diagnosed by BAL as malignant, 31 cases as suspicious/atypical which later on biopsy proved to benign lesions and were included in the false positive cases.…”
Section: 22supporting
confidence: 46%
See 1 more Smart Citation
“…Wongsurkait et al (1998) [8] 46.7% --Pirozynski et al (1992) [7] 64.8% --Present study 72% 100% 78.79% Of the 47 patients, 33 patients underwent simultaneous bronchoscopic biopsy. Out of the 15 benign cases diagnosed as BAL, 7 cases turned out to be false negatives.…”
Section: Discussionmentioning
confidence: 80%
“…Pirozynski et al (1992) [7] did a study on 145 patients of which 94 cases by BAL showed malignant cells. Wongsurkait et al (1998) [8] study on 55 radiological suspicious patients showed malignancy in 30 patients. BAL showed malignant cells in 14 cases out of the 30m positive cases.…”
Section: Discussionmentioning
confidence: 97%